School Climate: Conceptualization and Variables - Pérez-Guevara, Dayra-Julieth; Puentes-Suaréz, Alexandra-Inés (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This review aims to analyze the different conceptualizations of school climate and the variables related to the subject. The analysis is carried out based on the identification of 31 original articles, published in the databases Education Source, ScienceDirect, Scopus, Academic Search Premier and Taylor and Francis, in the period 2010 – 2020. Each text was read and analyzed by two reviewers, who recorded the information in a matrix built with content indicators. The results confirm that the school climate is conceptualized from the attributes of the organizational culture (norms, shared beliefs, values, and collective attitudes, teaching and learning practices). And it is analyzed from the group of perceptions of the educational actors (students, teachers, directors and parents) towards the characteristics of the academic, administrative and social environment structure, which in turn influence the behavior of the actors, the commitment to the teaching-learning processes and the way school life is experienced, and that favors or hinders academic, social and emotional development. In relation to the variables, it is highlighted that the positive perception of the students about the school climate is related to academic performance, emotional competencies, and school coexistence. In addition, in teachers with job satisfaction while the unfavorable perception of the school climate is associated with violence and school discrimination.